The Question of Man vs. Power in the Dystopian Writings: George Orwell’s 1984 - Bouslim, Ikram; Benatallah ,Sarah; Mouissa, Fattoum (University of Ammar Theledji -Laghouat, 2021)
Totalitarian ideology and policy were among the major topics that grabbed the attention of postmodern authors who committed their writing to criticize and researching them. George Orwell's final work, 1984, depicts life under a totalitarian government in a dystopian future. Accordingly, the objective of this dissertation is to study the totalitarian system in terms of the mental and physical changes that occur in the brains of the characters, notably the protagonist's. It sheds light on the physical and psychological sufferings that the protagonist endures. Likewise, it points to the different struggles that men underwent against the totalitarian regimes. The novel reveals that the painful experiences of most character could be attributed to the deprivation of rights as most characters were debased and dehumanized by tyrannizing regimes